ADAPTATION OF CHILDREN AND YOUNG PEOPLE DISPLACED FROM ARTSAKH IN THE EDUCATIONAL SYSTEM OF ARMENIA (EDUCATION IN THE 21ST CENTURY, 2023)
The relevance of this study is due to 2020 until now, with the uncertainty of the Armenian society, with the characteristic of "nօ war nor peace" societies since the years of independence, instability, and the ever-changing tension. This article aims to analyze the adaptation process in the educational system of children and youth displaced from Artsakh in 2020. The applied approach to the study of this problem is a combination of theoretical methods and empirical research, which allows a complex consideration of the problem of social adaptation of displaced children and youth. The use of theoretical methods made it possible to describe theoretical approaches in sociological, psychological and pedagogical studies of the phenomenon of social adaptation, characterized as a person's activity aimed at adapting the individual to the social environment and the conditions of being in that society. The article contains the results of the research conducted among children and young people displaced from Artsakh. The obtained data allow to identify the main adjustment problems for children and young people, draw conclusions and develop recommendations. The materials of the article are of practical importance for the design and implementation of short-term and long-term educational programs aimed at the adaptation of displaced children and youth. The main conclusion of the research is that the adaptation practices of children and youth in the educational system can be divided into the following groups: adequate and active adaptation, adequate and passive adaptation, and inadequate and passive adaptation. According to the sociology of adaptation, during drastic changes, passive adaptation prevails at the initial stage, but later the demand to face challenges conditions the spread of active adaptation. In theory, adequate adaptation is successful adaptation: a balance or harmony between the adapting subject and the environment. Adequate adaptation presupposes that the individual is aware of the nature of changes and challenges occurring in the environment and changes his consciousness and behaviour accordingly.
Keywords: education in Armenia; adaptation in education; displaced children and youth; post-war reality